Utilizing herbarium specimens to quantify historical mycorrhizal communities - Heberling, J. Mason (Appl Plant Sci, 2019)
PREMISE OF THE STUDY: Mycorrhiza are critical to ecosystem functioning, but a lack of historical baseline data limits our understanding of the long‐term belowground effects of global change. Herbarium specimens may provide this needed insight. However, it is unknown whether DNA of arbuscular mycorrhizal fungi (AMF) can be reliably extracted from vascular plant specimen roots. METHODS: We sampled roots from herbarium specimens of four herbaceous forest species collected in western Pennsylvania between 1881–2008. Using molecular methods (terminal restriction fragment length polymorphism and sequence analysis), we quantified AMF communities from specimen roots and tested for contamination. RESULTS: We successfully amplified AMF DNA from 44% (21/48) of the root but not leaf samples, indicating specimen contamination was negligible. As expected, there were significant differences in AMF composition between plant species (P < 0.05). However, no differences in AMF communities were detected through time, possibly due to limited sample size and low amplification rates in recent collections. DISCUSSION: Herbaria have potential as sources of valuable belowground microbial data to answer questions across geographic, temporal, and taxonomic scales otherwise not feasible. Ongoing methodological developments will only magnify this potential. Further tests are needed to determine curatorial practices that maximize this innovative use of herbarium specimens.